Burnout among Medical students: A literature review on prevalence, risk factors, and prevention strategies (Research, Society and Development, 2025)
Introduction: Burnout is a significant mental health issue among medical students, characterized by emotional exhaustion, depersonalization, and reduced personal accomplishment. Its prevalence in this population may exceed 40%, reflecting the heavy workload, performance pressure, sleep deprivation, competitiveness, and early exposure to human suffering. These factors make medical students particularly vulnerable to psychological distress. Objective: To analyze the prevalence of burnout, its main risk factors, and preventive strategies among medical students. Method: Observational and descriptive literature review based on scientific articles, systematic reviews, and meta-analyses available in PubMed, SciELO, and CAPES databases. Studies addressing burnout in medical students, its determinants, and preventive interventions were included. Results: A high prevalence of burnout was identified, with rates ranging from 30% to 50% depending on the assessment tool used. The most common risk factors included academic overload, sleep deprivation, financial difficulties, a hostile educational environment, and a history of mental disorders. Conversely, social support, quality of life, physical activity, mindfulness practices, mentoring programs, and institutional interventions demonstrated protective effects, reducing emotional exhaustion and promoting well-being. Conclusion: Medical students are at high risk for developing burnout, influenced by individual and institutional factors. Preventive strategies should involve structural changes in the academic environment, continuous psychological support, and the promotion of well-being and self-care practices, aiming to reduce psychological distress and foster the development of more resilient and emotionally balanced professionals.